Does The Efficient Market Theory In The Weak Form Exist? Evidence From Indonesia - Bram Hadianto; Hendrik Hendrik; Trishya Yuwana (Jurnal Manajemen Indonesia, 2021)
In the weak-form market efficiency theory, investors cannot predict the movement of all prices because of randomness. This circumstance happens because of a quick market reaction to new information. Conversely, suppose the market is not efficient in this shape; in that case, the investors can obtain an abnormal return. One of the reasons is the thin market, where many inactive stocks to be traded are available. Based on these issues, this research intends to examine this theory by employing runs testing on the daily returns of the Indonesia Composite Index (ICI) between January 2014 and December 2018 for each year and a whole. Once performing this test, this research demonstrates that the daily returns of the ICI are random for both situations. By denoting these facts, this research concludes that the capital market in Indonesia is efficient in a weak form and experiences a decrease in the thin level, reflected by the escalation in trading frequency, volume, and value, as well as the number of dynamic shares transacted. This research suggests that investors without sufficient information should utilize the service of the securities analysts to select the stocks they buy and sell to get the capital gain. Keywords – an efficient market in the weak form; market index return; runs test; thin market